2013
DOI: 10.5489/cuaj.807
|View full text |Cite
|
Sign up to set email alerts
|

The status of evidence-based medicine education in urology residency

Abstract: Introduction: Evidence-based medicine (EBM) is the conscientious, explicit, and judicious use of the current best evidence in decision-making for the care of patients. Teaching best evidence practice in residency should include both formal or freestanding content, as well as integration into clinical scenarios and patient care. We sought to assess the attitudes, experience and knowledge of EBM in urology residency training across Canada.Methods: An anonymous, cross-sectional, self-report questionnaire was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…Although all studies have consistently shown high degrees of acceptance of EBM training amongst those surveyed, considerable variation in the existence or format of EBM training programs has been reported. [8][9][10][11][12] For instance, a survey of urology program directors found that the majority of programs (78%) reported having a formal educational activity related to EBM but the allotted time varied significantly across different programs (4.8-25.0 hours per year) and the majority devoted less time than what they thought was ideal. 10 A survey of urology residents found that while an overwhelming majority of residents felt EBM is an important part of their curriculum, only 28% reported receiving formal EBM training in their program.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although all studies have consistently shown high degrees of acceptance of EBM training amongst those surveyed, considerable variation in the existence or format of EBM training programs has been reported. [8][9][10][11][12] For instance, a survey of urology program directors found that the majority of programs (78%) reported having a formal educational activity related to EBM but the allotted time varied significantly across different programs (4.8-25.0 hours per year) and the majority devoted less time than what they thought was ideal. 10 A survey of urology residents found that while an overwhelming majority of residents felt EBM is an important part of their curriculum, only 28% reported receiving formal EBM training in their program.…”
Section: Introductionmentioning
confidence: 99%
“…10 A survey of urology residents found that while an overwhelming majority of residents felt EBM is an important part of their curriculum, only 28% reported receiving formal EBM training in their program. 12 The 2 most commonly reported barriers to the teaching of EBM were lack of time and lack of qualified EBM educators. 10,12 Similarly, surveys of residents in other surgical specialties including otolaryngology and obstetrics and gynecology have found that there is insufficient formal training in their programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is stated that this situation results from the difference between teaching of courses in basic sciences and clinical sciences [25].It is known that assessments are conducted periodically in this instructional level since it is important to determine how well the content and goals are acquired. However, the lack of feedback from the trainings given within the scope of continuing education can be a reason why the number of studies focusing on this instructional level is so low [5].Another reason of the high number of studies focusing on pre-graduate level is the effort to give a comprehensive education despite the individual differences [25].Some researches on post-graduate level are known to be conducted with the aim of learning about the contemporary medicine literature [26].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was developed specifically for this survey and resulted from previous experiences with survey construction. [6][7][8] A limited number of residents and educators involved in postgraduate programs were asked to assess and modify the survey for clarity.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%